Big Data Management and Archival Practices: A Case Study of Omani Institutions Through Records Specialists’ Perspective - Mkadmi, Abderrazak; Hamad, Faten; Almaqbali, Mahmood Saif (Journal of Posthumanism, 2025)
This study delves into the current state and future potential of Big Data within Omani institutions, with a specific focus on insights provided by information and archives specialists. Employing a qualitative approach, the research conducts semi-structured interviews with 15 experts representing a diverse array of twelve Omani institutions, encompassing both public and private sectors. Participants were meticulously chosen based on their roles in records and archives management, supplemented by the involvement of IT specialists and administrative managers. The findings illuminate a nuanced understanding of Big Data within Omani institutions. While there exists a significant level of comprehension among staff regarding the complexities of Big Data, notable gaps persist in its practical application. Participants perceive Big Data as vast, diverse, and challenging data to manage, aligning with established scientific definitions. Formal education emerges as a critical avenue for knowledge acquisition, reflecting the evolving landscape where academic and professional domains intersect. Furthermore, interviews reveal the diverse nature of data within organizations, necessitating holistic management strategies and strategic investments in technology and security infrastructure. Key challenges such as data security, legal compliance, and the need for skilled human resources are underscored, emphasizing the necessity for specialized solutions and training programs. Moreover, the discussion extends to the future trajectory of records and information management, emphasizing the imperative of adapting to technological advancements and the continuous pursuit of education. Overall, this study offers valuable insights into the awareness, applications, transformations, governance procedures, and challenges associated with Big Data management within Omani institutions, as perceived by information and archives specialists.